PENGARUH LOKASI USAHA TERHADAP MINAT PEMBELIAN KONSUMEN - Sartika Jamlean; Saul Ronald Jacob Saleky; Victor R. Pattipeilohy (Jurnal Administrasi Terapan, 2022)
This study aims to analyze the effect of business location on consumer purchase intentions in Ambon City. For this reason, data was collected by means of questionnaires which were distributed to 100 sample people who were determined conventionally. Research data analysis was carried out using Simple Regression Analysis. The results of the analysis show that the business location has an influence of 99.1% while the remaining 0.9% is influenced by other variables that are not included in this study